Availability and Utilization of Assistive Technology for Learning among Students with Special Needs in Ilorin, Kwara State - Adebayo Emmanuel Alimi; Ebenezer Omolafe Babalola; Gboyega Ayodeji Aladesusi; Ahmed Idris Issa; Eyiyemi Veronica Omolafe (Indonesian Journal of Community and Special Needs Education, 2022)
The availability and use of technological devices to aid students with special needs in education and training are driven by the changing nature of work. This study investigated the Availability and Utilization of Assistive Technology for Learning among Students with Special Needs in Ilorin, Kwara State. A descriptive research design of survey type was employed for this study. Multi-stage sampling techniques of simple random sampling and purposive sampling were used to select 100 respondents for the study. The questionnaire was used for the study. Descriptive and Inferential statistics were used to answer the research question and test the stated hypotheses with the aid of statistical product and service solution (SPSS) version 20.0 at a 0.05 level of significance. The findings from this study showed that assistive Technology devices are available for assimilation of students with special needs in Ilorin, Kwara and there is no significant influence in the utilization of assistive technology for students of special needs based on the gender of the students. It was recommended that the Government should provide adequate funding to improve the availability of assistive technology.